Guiding Cultivar Choice In Smallholder Agriculture: Identifying Suitability Hotspots For Maturity Groups Of Field Crops - Grewer, U.; de Voil, P.; MacCarthy, D.S.; Rodriguez, D. (Resources, Environment and Sustainability, 2025)
The adoption of suitable crop cultivars is central to the sustainable intensification of smallholder cropping systems across Sub-Saharan Africa and plays a crucial role in improving smallholder incomes and food security. Breeding programmes have significantly increased the availability of early-, mid-, and late-maturing crop cultivars tailored to the Target Population of Environments in Sub-Saharan Africa. However, there is a substantial lack of data-driven maturity group recommendations at a detailed spatial scale. The absence of targeted guidance on the suitability of maturity groups limits the ability of smallholder farmers to make optimal cultivar adoption decisions. Here, we propose a framework using gridded crop modelling to identify locally relevant maturity group recommendations at a high spatial resolution for field crops. Implementing the framework for maize in Ghana, we employ the APSIM crop model across 3927 point locations and weather records for recent thirty years. We show that mid-maturing cultivars consistently provide the highest yields across all national production locations in the major growing season. In the minor growing season, we find that early- and mid-maturing cultivars provide the highest yields across distinct spatial suitability clusters. Specifically, in the minor growing season, mid-maturing cultivars provide the highest yields in high-yielding environments, while early-maturing varieties provide the highest yields in low-yielding environments. We identify specific environment-by-management combinations for which different maturity groups are optimal. The proposed framework enables the development of spatially and seasonally tailored maturity group recommendations that take advantage of prevailing genotype-by-environment-by-management interactions. The approach can readily be scaled to other crops and countries.
Research Article
Keywords: Sustainable intensification; Cultivar recommendations; Seed policy; Smallholder agriculture; Spatial analysis; Crop modelling